Analisis Minat Siswa dalam Membaca Al-Qur’an Melalui Ekstrakurikuler di SMP Negeri 3 Gombong - Handoko, Ilham Nur; Fatimah, Siti (IAINU Kebumen, 2024)
The aims of this research are 1) To analyze students' interest in reading the Al-Qur'an at SMPN 3 Gombong. 2) To describe the inhibiting factors and solutions in developing interest in reading the Al-Qur'an through extracurricular activities at SMPN 3 Gombong. This research uses a qualitative approach and a type of qualitative research with a field study approach. The data collection techniques use observation, interviews and documentation. The data analysis technique in this research is condensation collection, data presentation or display, and drawing conclusions or verification. The results of this research are that students who cannot read the Al-Qur'an at SMP N 3 Gombong are required to take part in the BTQ extracurricular so that students are able and interested in reading the Al-Qur'an. Inhibiting factors in developing interest in reading the Al-Qur'an through extracurricular activities at SMPN 3 Gombong include lack of student awareness and motivation, extracurricular implementation time, as well as comprehensive iqro' books and teacher human resources which need to be improved in terms of quantity and quality and related solutions. with these problems, namely effective and efficient time planning, varying other methods, providing encouragement for learning motivation, giving awards to students who can read the Koran, maximizing teachers to become BTQ extracurricular coaches, and the need for a strong commitment and a more comprehensive approach. teachers and students in implementing BTQ extracurricular activities.